Substantiation of the Optimal Sequence of industrial Building Reconstruction in Revitalization Projects, Taking into Account Their Future Function - Kravchunovska, T. S.; Balakin, K. V. (Science and Transport Progress, 2025)
Purpose. Development of a methodological approach to the revitalization of former transport infrastructure objects, taking into account their future function (functions) within the constraints of time and resources. Methodology. A systems approach to modelling the revitalization process in terms of substantiating the sequence of inclusion of non-functioning transport infrastructure objects in the project; a comprehensive approach to forming a set of determining factors of exogenous and endogenous nature. Findings. A methodological approach to the revitalization of former transport infrastructure objects has been improved, taking into account the preservation of the authenticity of buildings, the adaptive use of their space, the application of building information modelling technologies, artificial intelligence, the Internet of Things, selective dismantling of structures, and soil remediation to meet safety, comfort, inclusiveness, and energy efficiency requirements, ensuring the commissioning of objects with specified technical and economic characteristics within existing resource constraints. Originality. A systems approach has been applied to the organization of the revitalization processes of former transport infrastructure objects, which involves a step-by-step analysis of the sequence of transformation of buildings and structures, taking into account the determining factors influencing the choice of their future function; at the same time, the tasks of transforming urban development by rethinking the functions of existing buildings instead of constructing new objects correlate with the tasks of creating sustainable housing, economic growth, responsible production and consumption. Practical value. The task of transforming urban development by rethinking the functions of existing industrial buildings instead of constructing new objects correlates with the tasks of creating sustainable housing, economic growth, responsible production and consumption. The proposed approach to determining the optimal sequence for the reconstruction of unused transport infrastructure objects with a change in their functional purpose in revitalization projects allows priorities to be set taking into account the influence of a number of determining factors and provides state authorities, local self-government bodies and investors with tools for making effective decisions under time and resource constraints, taking into account technical, legal and financial aspects.